PENGARUH SKEPTISME PROFESIONAL AUDITOR TERHADAP KETEPATAN PEMBERIAN OPINI PADA BADAN PEMERIKSA KEUANGAN RI PERWAKILAN SULAWESI SELATAN - Chairul Ihsan Burhanuddin (AkMen JURNAL ILMIAH, 2018)
This study was conducted to see how big the skepticism of professional auditors to the accuracy of giving opinion. The sample obtained as many as 71 respondents auditors at the State Audit Board (BPK) RI Representative of South Sulawesi Province. In accordance with the above purposes, in this study formulated two hypotheses. The first hypothesis, partially (individual) mepunyai significant influence of auditor professional skepticism to provide opinion auditors. The second hypothesis, partially (individually) does not have a significant effect of skepticism of professional auditors on giving opinion of auditors, this research is conducted by using simple linear regression analysis method with the help of SPSS 20.0. The results of this study are: skepticism professional auditors have a significant effect on giving opinion auditors. Suggestions for further research, should add to the sample and expand the scope of the study, considering other variables that are still closely related to the variables in this study.